(untitled) (Journal of Information Technologies in Education (ITE), 2011)
This paper explains the need and provides the main stages of the development of new curricula "Mathematical analysis" for students training areas - computer science, which includes the study of the possible applications of mathematical analysis in information processing algorithmic methods using computer technology.